DAMPAK MINUMAN KERAS SOPI TERHADAP PERILAKU REMAJA DITINJAU DARI PERSPEKTIF KESEJAHTERAAN SOSIAL STUDY DESKRIPTIF DI DUSUN YAWURU KECAMATAN PULAU-PULAU TERSELATAN KABUPATEN MALUKU BARAT DAYA - Josephus Noya (JURNAL BADATI, 2023)
Sopi is a typical traditional drink from Maluku with a high level of consumption in society. Sopi drinks are like prohibited drugs that are specifically consumed at certain times, such as the ongoing activities of traditional events in the community. The availability of sopi in traditional events is a tradition from the ancestors in ancient times until now. Traditional sopi drinks are used in traditional events including traditional weddings, traditional family parties, ecclesiastical events and traditional rituals of the State. Consuming sopi can be allowed to carry out sibling relationships in customary ties, where consuming sopi can have two impacts, namely negative and positive on the human body, mental and social life. The alcohol contained in coffe drinks is ethanol (CH3, CH2, OH) from fermented sap which has been distilled, the purpose of this study is to find out and analyze the impact of consuming sopi liquor on adolescent behavior in Yawuru Hamlet, Pulau-Selatan District, West Maluku Regency Daya, as input to increase knowledge for IKS (Social Welfare) majors on the one hand and on the other hand can increase knowledge for students, the results of the study explain that there are factors that influence adolescents to consume sopi drinks such as promiscuity and the influence of the outside environment. This is what causes the impact on adolescent behavior such as fighting, brawls and dropping out of school.